Studies on oxidative enzymes (polyphenol oxidase and peroxidase) in four varieties of banana (Musa paradisiaca L.) under the pathogenesis of three fruit-rot fungi - S.GIRISHAM* and S.M. REDDY, SUPRIYA SARKAR, P. SHILPA (Indian Phytopathology, 2010)
Involvement of oxidative enzymes-polyphenol oxidase and peroxidase in relation to the genetical varieties (Cavendish, Rasthali, Poovan and Curry) of banana (Musa paradisiaca L.) under the pathogenesis of Macrophomina phaseolina, Fusarium oxysporum and Nigrospora oryzae was investigated. Polyphenol oxidase and peroxidase activities in diseased fruits underwent significant change in response to the pathogens infection. However, the degree of changes varied both with the variety and the pathogen involved. In general an increase in polyphenol oxidase and peroxidase activity was recorded upto 8th day of inoculation in Cavendish variety, while in other three varieties, an increase in enzyme activity was recorded upto 6th day. The increase was more significant in M.phaseolina infected fruits followed by F.oxysporum and N. oryzae. In Rasthali and Poovan varieties the increase in polyphenol oxidase and peroxidase was recorded upto 6th day of inoculation in course of infection by three fruit-rot fungi under study. On the other hand, in Curry variety the polyphenol oxidase and peroxidase activity was not much significant.